2013
DOI: 10.1016/j.fob.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma irradiation on mistletoe (Viscum album) lectin‐mediated toxicity and immunomodulatory activity

Abstract: This study evaluated the effect of gamma irradiation on the reduction of the toxicity of mistletoe lectin using both in vitro and in vivo models. To extract the lectin from mistletoe, an (NH4)2SO4 precipitation method was employed and the precipitant purified using a Sepharose 4B column to obtain the pure lectin fraction. Purified lectin was then gamma-irradiated at doses of 0, 5, 10, 15, and 20 kGy, or heated at 100 °C for 30 min. Toxic effects of non-irradiated, irradiated, and heat-treated lectins were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
(33 reference statements)
2
11
0
1
Order By: Relevance
“…Based on the above results, our finding indicates that gamma irradiation clearly decreases the toxicity of doxorubicin on nontarget cells. These results are in agreement with findings of Sung et al (2013) and Kim et al, (2009), who concluded that gamma irradiation could be regarded as a potential method for reducing the immunological toxicity of anti-cancer drugs including doxorubicin. Therefore, the gamma irradiation could be considered as a useful technology for the reduction of the toxicity of the anticancer drug lectin without compromising its bioactivity.…”
Section: Exposure Dose (Gy)supporting
confidence: 92%
See 1 more Smart Citation
“…Based on the above results, our finding indicates that gamma irradiation clearly decreases the toxicity of doxorubicin on nontarget cells. These results are in agreement with findings of Sung et al (2013) and Kim et al, (2009), who concluded that gamma irradiation could be regarded as a potential method for reducing the immunological toxicity of anti-cancer drugs including doxorubicin. Therefore, the gamma irradiation could be considered as a useful technology for the reduction of the toxicity of the anticancer drug lectin without compromising its bioactivity.…”
Section: Exposure Dose (Gy)supporting
confidence: 92%
“…Dε Â 10 8 f c (Hz) of these drugs to radiation were to enhance their functional activity on tumour cells (Smeltzer et al, 2015;Sung et al, 2013), for sterilization purposes (Maksimenko et al, 2008;Varshney & Dodke, 2004) or to reduce their immunological toxicity (Kim et al, 2009). The objective of this study was to evaluate the effect of gamma irradiation on the structural stability of one of the most famous anticancer drugs, doxorubicin, (DOXO) (Varshney & Dodke, 2004).…”
Section: Exposure Dose (Gy)mentioning
confidence: 99%
“…Irradiation technique is more popular than chemical and other physical mutagenesis (IAEA 2012) because irradiation is rapid, convenient and more extensive and the ionizing energy penetrates rapidly through the polysaccharide granule (Bao et al 2005). The most popular irradiation is gamma ray irradiation from Co 60 which is widely used in agriculture (Piri et al 2011) as a mutagenesis agent for large commercial crops like ornamental plants (Barakat and El-Sammak 2011), food crops (IAEA 2012), pharmaceutical plants (Sung et al 2013) and oil palm (Rohani et al 2012).…”
Section: Effect Of Gamma Irradiation On the Growth And Development Ofmentioning
confidence: 99%
“…It indicates that treatments of gamma irradiation up to 20 Gy increased somatic embryo formation in sago palm. Gamma ray irradiation has been successfully applied in many crops for in vitro mutagenesis (Barakat and El-Sammak 2011;IAEA 2012;Sung et al 2013). The somatic embryos of sago palm were able to regenerate into small shoots in the following 4 to 6 weeks of culture.…”
Section: Somatic Embryo Inductionmentioning
confidence: 99%
“…Inpatient health-care institutions are increasingly adopting disease-specific order sets [1,2] to decrease practice variation, promote evidence-based practice, improve efficiency [3], decrease the rate of medication errors [4,5] and adhere to practice guidelines [6,7]. Available quantitative research is limited and has been done by few institutions to assess the impact of disease-specific standardized orders.…”
Section: Introductionmentioning
confidence: 99%